PEMBONCENG GRATIS GERAKAN REFORMASI DI INDONESIA - Robert Mirsel (Jurnal Ledalero, 2014)
Free-rider is one of the problems faced in many social movements. The problem is with those who benefit much from a social movement while never investing, or invest very little, into the movement; meanwhile those who invest and sacrifice much get almost nothing from it. This study is an attempt to explore whether or not there is a free rider phenomenon in the Reformation Movement in Indonesia. The findings of studies show that the Reformation Movement did not bring about significant change for most people in Indonesia except for the free riders: the politicians, top military officials, and big corporations (entrepreneurs) who were once part of the previous Suharto Regime. This study suggests that there should be change in the strategies and tactics of the movement to prevent a free rider problem and give more opportunities to people at the grassroots to benefit from the movement. Kata-kata kunci : Gerakan reformasi, agenda reformasi, pembonceng gratis, masalah pembonceng gratis, revitalisasi gerakan reformasi.